EXPLORING THE ANTI-PARKINSONIAN POTENTIAL OF CASSIA TORA ETHANOLIC LEAVES EXTRACT IN ANIMAL MODELS - Mishra, Bandana; Ray, Jassaswi; Prusty, S.K.; Mohanty, Rajashree; Patra, Anup Ku (Journal of Global Pharma Technology, 2024)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by motor impairments resulting from the loss of dopaminergic neurons. Current treatments provide symptomatic relief but do not halt disease progression. In this study, we investigated the potential therapeutic effects of Cassia tora ethanolic leaves extract (CTELE) on PD using animal models. CTELE, known for its rich bioactive compounds, was administered orally to PD-induced animals, and their behavioral responses were assessed using standard motor function tests. Additionally, histopathological examination and biochemical assays were performed to evaluate the neuroprotective mechanisms of CTELE. Our results demonstrate that CTELE treatment ameliorated motor deficits in PD animal models, as evidenced by improved locomotor activity and coordination. Furthermore, histological analysis revealed a preservation of dopaminergic neurons in the substantia nigra pars compacta of CTELE-treated animals compared to untreated controls. Biochemical analysis showed a reduction in oxidative stress markers and an increase in antioxidant enzyme activity in CTELE-treated animals, suggesting its potential neuroprotective effects. These findings suggest that CTELE may hold promise as a natural therapeutic agent for PD and warrant further investigation into its underlying mechanisms of action and clinical efficacy. Keywords: Cassia tora leave, Parkinson’s disease.